Biomarker characteristics and geological significance of middle and upper Permian source rocks in the southeastern Junggar Basin. (2nd October 2019) - Qu, Yongqiang; Tao, Huifei; Ma, Dongzheng; Wu, Tao; Qiu, Junli
Abstract: Total organic carbon content (TOC), carbon isotope and biomarker analysis have been done on the source rocks from Lucaogou and Wutonggou formations in Junggar Basin, NW China. (1) the TOC values of the source rocks are more than 5%, and the kerogen types are type I1 -II, and the organic matters are mainly algae and bacteria, and are in the mature stage. (2) the depositional environments of the source rocks are weak reduction-weak oxidation, and are of weakly salty water to brackish water environment.